2001
DOI: 10.1093/brain/124.4.826
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of presynaptic inhibition and disynaptic reciprocal Ia inhibition during voluntary movement in spasticity

Abstract: The aim of the study was to investigate whether impaired control of transmission in spinal inhibitory pathways contributes to the functional disability of patients with spasticity. To this end, transmission in the pathways mediating disynaptic reciprocal Ia inhibition and presynaptic inhibition was investigated in 23 healthy subjects and 20 patients with spastic multiple sclerosis during ankle dorsiflexion and plantar flexion. In healthy subjects, but not in spastic patients, the soleus H reflex was depressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
130
1
16

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(151 citation statements)
references
References 38 publications
4
130
1
16
Order By: Relevance
“…These effects are mediated via the muscle spindle of the flexor group Ia afferents, and the pathway involved is known as reciprocal Ia inhibition (Tanaka 1974;Crone et al 1987;see review in Crone 1993). This reflex inhibition is reported to decrease considerably, and be eliminated during voluntary movement in individuals with established SCI (Boorman et al 1996a;Morita et al 2001;Crone et al 2003), contributing to spasticity and to poor movement performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects are mediated via the muscle spindle of the flexor group Ia afferents, and the pathway involved is known as reciprocal Ia inhibition (Tanaka 1974;Crone et al 1987;see review in Crone 1993). This reflex inhibition is reported to decrease considerably, and be eliminated during voluntary movement in individuals with established SCI (Boorman et al 1996a;Morita et al 2001;Crone et al 2003), contributing to spasticity and to poor movement performance.…”
Section: Introductionmentioning
confidence: 99%
“…This reflex depression is attributed to presynaptic inhibition of soleus Ia afferents (reviewed in Katz 1999). In human SCI, modulation of Ia input is diminished under both static (Faist et al 1994;Morita et al 2001) and dynamic (Yang and Whelan 1993) conditions, suggesting that the timely regulation of presynaptic inhibition at the onset of stretch or movement in these patients might be lost.…”
Section: Introductionmentioning
confidence: 99%
“…The balance between the excitatory and inhibitory synaptic inputs may be altered as a result of the removal of descending drive to the motoneurons, interneurons, and presynaptic terminals (e.g., Refs. 3,26). The motoneurons of paralyzed muscles may receive new inputs from axons that have sprouted from neighboring cells (for reviews see Refs.…”
mentioning
confidence: 99%
“…Impairment of rTMS modulates reciprocal inhibition in SCI patients R Nardone et al reciprocal inhibition has been suggested to have a causal role in the development of spasticity, 6,14-17 and a decreased excitability in the disynaptic reciprocal inhibitory pathway has indeed been demonstrated in patients with spasticity of different origin. 14,17,18 TMS studies in awake humans have already demonstrated cortical control of spinal reflex circuits. In fact, subthreshold TMS produces a short-latency inhibition on the soleus H-reflex followed by a period of facilitation, [19][20][21] whereas the TA H-reflex is facilitated at an early conditioning-test interval.…”
Section: Discussionmentioning
confidence: 99%